Exploring the Influence of Mall on Academic Stress Affecting Students' English Speaking Skills - Salamah, Nafis Daris; Ferdiyanto, Feri; Zainuddin, Zainuddin (Universitas Pahlawan Tuanku Tambusai, 2026)
English speaking skill is important in the digital era, but many junior high school students still feel academic stress and anxiety when they have to speak English. Although Mobile-Assisted Language Learning (MALL) has often been studied to improve language achievement, most research focuses on test results and numbers. Only a few studies discuss students’ real experiences and how MALL affects their academic stress. This study aims to explore the influence of MALL on academic stress and English speaking skills of ninth-grade students at SMP Plus Tahdzibun Nasyiin. This research used a qualitative case study. Data were collected from 15 students through interviews, classroom observations, and speaking task documentation. The results show that MALL helps students practice more freely and confidently, improve pronunciation and vocabulary, and reduce anxiety, although technical problems and distractions can still cause stres.